The mediator role of leader-member exchange in empirical test - Abdul Haeba Ramli (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
The purpose of this research is to determine the effect of procedural justice and leader-member exchange on job satisfaction. This is a cross-sectional research with data collected from 100 employees of private sector services using a questionnaire and analyzed with the Likert scale. The result showed the following (1) procedural justice has positive and significant effect on leader-member exchange, (2) leader-member exchange has a positive effect on job satisfaction, (3 procedural justice has a positive and significant effect on job satisfaction, and (4) leader-member exchange mediates the effect of procedural justice on job satisfaction. Therefore, private companies are encouraged to strengthen systems and work procedures that are fair to employees with positive impacts. In conclusion, companies need to provide intensive training for Leaders and supervisors to increase the potential and abilities of employees, thereby making them more enthusiastic, enterprising, happy, and diligent in carrying out their duties.